Evaluation of renal fibrosis in patients with chronic kidney disease by shear wave elastography: a comparative analysis with pathological findings. - Chen, Ziman; Chen, Jiaxin; Chen, Hui; Su, Zhongzhen (Abdominal Radiology, 2022)
Purpose: To explore the elastic values obtained by shear wave elastography (SWE) in assessing renal fibrosis in chronic kidney disease (CKD). Methods: One hundred and twenty-four patients with CKD who underwent renal biopsy were prospectively enrolled between April 2019 and June 2021. SWE was performed to measure the renal cortex stiffness, presented as SWE parameters, including the minimum, mean, and maximum elasticity (namely Emin, Emean, and Emax). Then, the patients with different kidney pathological impairment (mild, moderate, and severe groups) were compared in SWE elasticity and the discriminative capacity was also analyzed. Results: For the pathology impaired grade, SWE parameter was significantly reduced in the moderately and severely impaired group than the mild one. Emax parameter achieved the best discriminative ability toward differentiating moderate–severe impairment from mild one, yielding an area under the curve (AUC) of 0.764 (95%CI: 0.681–0.848). Regarding interstitial fibrosis/tubular atrophy and global glomerular sclerosis, the Emax values were significantly reduced across the group of patients with moderate grade compared to those with mild grade. Patients in severe group were also with reduced elastic value than those in mild one, while the difference was non-significant in interstitial fibrosis/tubular atrophy but a borderline statistical significance was achieved in global glomerular sclerosis. For grade of vessel wall thickening, patients in moderate (33.04 ± 9.86 kPa, P = 0.009) and severe (31.42 ± 9.16 kPa, P < 0.001) group were with significantly lower elastic value compared with those in the mild one (39.58 ± 9.67 kPa). The SWE parameter was linearly reduced as grade of vessel wall thickening elevated (P for trend: < 0.001). Conclusion: SWE derived elastic values reduced as pathology grade of renal fibrosis or grade of vessel wall thickening progresses in patients with CKD, which may be attributed to renal hypo-perfusion rather than tubulo-interstitial fibrosis progression.